Efficiency of laparoscopic artificial insemination in goats: impact of laparoscopic insemination sheath needle design - Kang, Ting-Chieh; Lin, Hsin-Hung; Lin, Hsiu-Lien; Tsai, Pei-Chun; Chen, Yu-Hsin; Chu, Fung-Hsiang; Tseng, Kai-Fei; Lai, I-Ling; Shen, Perng-Chih (Frontiers in Veterinary Science, 2025)
IntroductionLaparoscopic artificial insemination (LAI) is widely used in goat breeding, yet the influence of sheath needle design on reproductive outcomes remains unclear. This study aimed to evaluate the effects of three different LAI sheath designs (IMV, Minitube, and TLRI) on pregnancy rate, kidding rate, and average litter size in Alpine does.MethodsA total of 300 Alpine does (2–3 years old) were enrolled in two experiments. In Experiment 1, does were inseminated into either the middle-horn (M-H) or the horn-body junction (H-BJ) of one uterine horn using each of the three sheath types. In Experiment 2, the IMV and TLRI sheaths were used to deposit semen either unilaterally or bilaterally. Pregnancy rate, kidding rate, and average litter size were recorded for all treatment groups. Statistical significance was set at p < 0.05.ResultsIn Experiment 1, overall pregnancy rates with TLRI and IMV sheaths were significantly higher than with the Minitube sheath (p < 0.05) regardless of site. The lowest kidding rate occurred with the Minitube sheath at the H-BJ site (p < 0.05), while the highest was observed with the TLRI sheath at the M-H site (p < 0.05). No significant differences in kidding rate or average litter size were found among the remaining groups (p > 0.05). In Experiment 2, there were no significant differences in pregnancy rate, kidding rate, or average litter size between unilateral and bilateral inseminations using either the IMV or TLRI sheath (p > 0.05).DiscussionThese findings demonstrate that both TLRI and IMV sheath designs outperform the Minitube sheath in terms of pregnancy and kidding rates, particularly when targeting the M-H site. Moreover, unilateral insemination with these sheaths does not compromise reproductive performance and offers a time-efficient alternative to bilateral deposition. Adoption of optimal sheath designs and insemination strategies can enhance LAI efficiency and success in goat breeding programs.